Implementasi Subrogasi dengan Lastgeving Sebagai Instrument Hukum Dalam Peralihan Hak Atas Tanah - Yunesha Ratih Fitriani (Lex Renaissance, 2017)
AbstractThe focus of this study is to explain the implications of their subrogation by granting power of attorney involved in the transition lastgeving land rights and outlining efforts to settle the implications of  the implementation of the application of subrogation by giving power of attorney lastgeving in the turnover of land rights. This research is a normative approach doctrinal and non-doctrinal. Results showed positive implications, namely the debt of the debtor be paid, the creditor will obtain repayment of debt and the third party will acquire the land and building. The implication negative is about the costs, expenses and Roya who from the beginning was not discussed so that a dispute exists between the seller and the buyer, not made a deed of power of a debt by a notary during the process of debt repayment in the bank, bad credit by the purchaser which replaced debtors, banks that do not receive transition without notice to the bank first. For his efforts in general notary prepare and notify to the parties to the costs of the burden of transition, the cost Roya, on payment of taxes, as well as supplies of administration, and the notary from the beginning to tell and gives advice on the consequences that ensue for the switchover without the knowledge of the bank so that no losses of the parties in the future.Keywords: Subrogation, Authorization Deed Lastgeving, Transfer of Rights to Land